2011
DOI: 10.1136/jamia.2010.006502
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' opinions of a health information exchange: Table 1

Abstract: Respondents reported that AMIE had the potential to improve care, but they felt that AMIE impact was limited due to the data available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 27 publications
2
64
0
Order By: Relevance
“…The results indicated that a greater volume of information, including data about a larger variety of medical services, flows from the tertiary-care hospital to the clinics compared with the information flow in the opposite direction. Hincapie et al 20 concluded in a focus group study of 29 physicians who have experienced the Arizona Medical Information Exchange program that the data availability in the system would be the limiting factor in realizing the expected effects of the technology, and the finding implies that the benefit potential of the technology would be larger in clinics than in hospitals. We found in both the pre-implementation and the postimplementation survey that information containing pathology and lab results, diagnostic imaging, medication, and working diagnosis were the most needed and valued by physicians in both practice settings, which implies a potential of the HIE for saving healthcare costs by reducing duplicate lab or imaging tests and improving the quality of care by assisting physicians in clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that a greater volume of information, including data about a larger variety of medical services, flows from the tertiary-care hospital to the clinics compared with the information flow in the opposite direction. Hincapie et al 20 concluded in a focus group study of 29 physicians who have experienced the Arizona Medical Information Exchange program that the data availability in the system would be the limiting factor in realizing the expected effects of the technology, and the finding implies that the benefit potential of the technology would be larger in clinics than in hospitals. We found in both the pre-implementation and the postimplementation survey that information containing pathology and lab results, diagnostic imaging, medication, and working diagnosis were the most needed and valued by physicians in both practice settings, which implies a potential of the HIE for saving healthcare costs by reducing duplicate lab or imaging tests and improving the quality of care by assisting physicians in clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Advocates of health IT point to innovations, including digital radiology, electronic medical records, and computerized physician order entry as tools to enhance clinical productivity. 12,13 Our results suggest that surgical residents may also recognize improvements in hospital IT as an important way of increasing efficiency, thereby allowing greater opportunities for time to be devoted toward education. Additionally, the high rating of health IT as a benefit to education may incorporate and reflect the immediate availability of digital and web-based educational resources.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have identified missing information as a significant barrier to HIE utilization. (17)(18)(19) In our project, participants reported that they rarely found the prescription information they queried.…”
Section: Discussionmentioning
confidence: 99%